2021
DOI: 10.1097/won.0000000000000745
|View full text |Cite
|
Sign up to set email alerts
|

Italian Guidelines for the Nursing Management of Enteral and Urinary Stomas in Adults

Abstract: PURPOSE: This article is an executive summary of Italian guidelines for nursing management of enteral and urinary ostomies in adults. METHODS: Scoping review and generation of evidence and consensus-based clinical guidelines. SEARCH STRATEGY: The Multidisciplinary Italian Study group for STOmas (MISSTO) was founded in 2018. This group created guidelines for management of enteral and urinary ostomies in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 88 publications
0
28
1
Order By: Relevance
“…However, a smaller study by Salvadalena45 found an incidence of less than 3%. Italian Guidelines for the Nursing Management of Enteral and Urinary Stomas in Adults15 advised against the use of convexity during the first postoperative days. However, the panel strongly supported that finding a pouching system that can achieve predictable wear time was the overriding goal and determined that the risk of mucocutaneous separation that can be managed with effective wound care did not outweigh this fundamental goal of care 43,46,47.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a smaller study by Salvadalena45 found an incidence of less than 3%. Italian Guidelines for the Nursing Management of Enteral and Urinary Stomas in Adults15 advised against the use of convexity during the first postoperative days. However, the panel strongly supported that finding a pouching system that can achieve predictable wear time was the overriding goal and determined that the risk of mucocutaneous separation that can be managed with effective wound care did not outweigh this fundamental goal of care 43,46,47.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26] A single clinical practice guideline from the Multidisciplinary Italian Study Group for Stomas was identified that advised against the use of a convex pouching system during the "first postoperative days" due to concerns regarding the potential for mucocutaneous separation. 15 This recommendation was based on expert opinion rather than supporting evidence and the time frame was not further identified. Based on these apparent gaps in evidence and paucity of best practice guidance, the panel moved forward with generation of best practice statements guiding the use of convexity during the postoperative period.…”
Section: Findings: Scoping Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 , 3 Best practice guidelines consistently recognize that a secure seal around the stoma is required to minimize leakage that is associated with peristomal skin complications and diminished health-related quality of life. 4 6 …”
Section: Introductionmentioning
confidence: 99%